The Influence of Psychological Capital and Digital Literacy on Work Readiness Among Final Year Student at Semarang State University - Nabila Nova Azzahra; Rossi Galih Kesuma (Yayasan Minang Darussalam, 2026)
Work readiness among final-year university students remains suboptimal despite its critical role in determining a successful transition into the workforce. This study aimed to examine the influence of psychological capital and digital literacy on work readiness among final-year students at Semarang State University (UNNES). This research employed a quantitative correlational approach. The population consisted of 5,228 students, with a sample of 331 final-year students drawn using proportionate random sampling. Data were collected using three adapted psychological scales and analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results of the analysis show that psychological capital and digital literacy have a simultaneous effect on the work readiness of final-year students at UNNES, with a calculated F-value of 227,673 and p = 0.000 < 0.05. Partially, psychological capital has an effect with a t-value of 6,124, followed by digital literacy which has a dominant effect with a t-value of 17,527. Together, both variables contributed 58.1% to work readiness, while the remaining 41.9% was attributable to other factors beyond the scope of this study, including soft skills, internship experience, and social support. These findings offer practical implications for universities need to develop student oriented programs that build psychological capital while also improving digital literacy in preparing graduates for the competitive labor market.